Taxonomic Analysis of Honey-Juicy Plants of Karakalpakstan (Texas Journal of Agriculture and Biological Sciences, 2024)
Nowadays, the bee-keeping is considered one of the getting developed field in the Republic of Uzbekistan. As we know, honey products are used not only in medicine to recover some diseases but also in cosmetology and confectioneries.